Isolation of formononetin-7-O-β-D-glucopyranoside from the grass of Ononis arvensis L. and the assessment of its effect on induced platelet activation - A. M. Bogoutdinova; A. K. Whaley; A. O. Ponkratova; A. A. Orlova; M. Yu. Goncharov; V. S. Shpakova; N. T. Farmanova; D. Kh. Nurullaeva; A. T. Sharipov; S. P. Gambaryan; M. N. Povydysh (Разработка и регистрация лекарственных средств)
Introduction. Analysis of the clinical and laboratory picture of the SARS-CoV-2 infection suggests the presence of microcirculation and oxygen transport disorders, hemolysis of erythrocytes, intra-alveolar fibrin formation and microthrombus formation in the patient’s pathogenesis. Accordingly, the search for potential anticoagulants, erythrocyte antiplatelet agents, membrane stabilizing drugs and mild thrombolytic drugs can prevent the development of life-threatening complications and reduce the mortality of COVID-19 patients.Aim. Isolation of formononetin-7-O-β-D-glucopyranoside from the grass of Ononis arvensis L. and identification of the molecular mechanisms of its effect on platelet activation in vitro, induced by TRAP-6 (Thrombin receptor activated peptide) and ADP (adenosine diphosphate).Materials and methods. Terrestrial parts of Ononis arvensis L. were collected in the SPCPU nursery of medicinal plants (Leningrad region, Vsevolozhsky district, Priozerskoe highway, 38 km). Isolation of formononetin-7-O-β-D-glucopyranoside was carried out by preparative high performance liquid chromatography on a Smartline device (Knauer, Germany) equipped with a spectrophotometric detector. The structure of formononetin-7-O-β-D-glucopyranoside was confirmed by one-dimensional and two-dimensional NMR spectroscopy (Bruker Avance III, 400 MHz, Germany), as well as high-resolution mass spectrometry (HR-ESI-MS) (Bruker Micromass Q-TOF, Germany). The study of the effect of formononetin- 7-O-β-D-glucopyranoside on induced platelet activation was carried out on human platelets isolated from the blood of healthy volunteers. To research the effect of formononetin-7-О-β-D-glucopyranoside on platelet aggregation flow cytofluorometry with Cyto-FLEX (Beckman-Coulter, USA) was used.Results and discussion. According to the method of fractionation and purification of the total extract of O. arvensis developed in previous studies, formononetin-7-O-β-D-glucopyranoside was isolated in an individual form for subsequent biological studies with a total yield of 30 % in comparison with its content in the original extract. In samples with formononetin-7-O-β-D-glucopyranoside and ADP, there is a pronounced inhibition of platelet activation – the percentage of active platelets ranges from 6.3–6.6 % at doses of formononetin-7-O-β-D-glucopyranoside 1 μM, 3 μM and 30 μM. The inhibitory effect of formononetin-7-O-β-D-glucopyranoside is not dose-dependent (p ≤ 0.05). In samples with formononetin-7-O-β-D-glucopyranoside and TRAP, there is also a pronounced inhibition of platelet activation. The percentage of active platelets is 8 % at 1 μM formononetin-7-O-β-D-glucopyranoside doses, 15 % at 3 μM doses, and 16 % at 30 μM doses.Conclusion. Administration of formononetin-7-O-β-D-glucopyranoside at doses of 1 μM, 3 μM, 30 μM strongly inhibits platelet activation induced by ADP and TRAP-6. For ADP, there is no dose-dependent effect, while for TRAP there is a weak dose-dependent effect, the greatest inhibition efficiency is achieved with the minimum investigated dose of 1 μM. In all cases, the results obtained are statistically significant.